Sarcopenic Obesity Indices Are Major Determinants of Bone Strength in Older Adults With Obesity - Gregori, Giulia (J Endocr Soc, 2021)
Background: The increasing number of older adults with obesity is a growing public health problem because of increased risk of fractures especially at the ankle and upper leg despite normal or high bone mineral density. Among the contributory factors for fracture risk in this population may be aging- and obesity- associated physical frailty and impaired bone quality. However, how the adverse changes in physical function and body composition in this aging and obese population contribute to bone quality as assessed by finite element analyses (FEA) of bone strength has not been determined. Methods: One-hundred sixty-nine older (age ≥ 65 yrs.) adults with obesity (BMI ≥ 30 kg/m(2)) were recruited to participate in lifestyle intervention trials at our Medical Center. All underwent baseline measurements of bone strength (failure load [N] and stiffness [N.mm(-1)]) as estimated using FEA from high-resolution peripheral quantitative tomography (HR-pQCT) of the distal radius and tibia. In addition, body composition (appendicular lean mass/BMI [ALM(BMI)], fat mass/height(2) [FMI]) was assessed by dual-energy x-ray absorptiometry (DXA) and physical function by the modified physical performance test (PPT), knee extension strength (isokinetic dynamometry), hand grip strength, and 4-meter gait speed. Results: Bivariate analyses showed that ALM(BMI) (r=.57 to .58), FMI (r=-.16 to -.17), gait speed (r=.20 to .21), grip strength (.56 to .57), and knee extension strength (r=.40 to .42) correlated with stiffness and failure load at the distal radius (all P<0.05). In addition, ALM(BMI) (r=.65 to .67), FMI (r=-.22 to .23), gait speed (r+.18 to .19), grip strength (r=.58 to .59), and knee extension strength (r=.44 to .45) correlated with stiffness and failure load at the distal tibia (all P<0.05). Controlling for age and sex, multiple regression analyses revealed that ALM(BMI) (β=.34 to .35) and grip strength (β=.28 to .29) were the independent predictors of stiffness and failure load at the distal radius, explaining 45% to 46% of the variance in stiffness and failure load (P<0.001). On the other hand, multiple regression analyses revealed that ALM(BMI) (β=.45 to .52), grip strength (β=.27 to .28), and FMI (β=.17 to .18) were the independent predictors of stiffness and failure load at the distal tibia, explaining 74% to 75% of the variance in stiffness and failure load (P<0.001). Conclusions: These findings suggest the importance of preserving muscle mass while reducing fat mass and improving physical function to maintain bone quality and decrease the risk of fractures when older adults with obesity undergo lifestyle intervention.